2014
DOI: 10.1371/journal.pone.0089149
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Nociceptive Activities of Methanol Extract from Aerial Part of Phlomis younghusbandii Mukerjee

Abstract: This study was designed to investigate the anti-inflammatory and anti-nociceptive activity of the methanol extract from the aerial part of Phlomis younghusbandii (MEAP) and to explore the possible related mechanisms. Anti-inflammatory effects of MEAP were evaluated by using the ear edema test induced by dimethylbenzene and vascular permeability test induced by acetic acid. Anti-nociceptive activities of MEAP were evaluated by the chemical nociception in models of acetic acid-induced writhing and formalin-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
(33 reference statements)
1
18
0
1
Order By: Relevance
“…It has been reported that Phlomis Radix can be used to treat RA (26). For instance, Wang et al (27) demonstrated that the methanol extract from the aerial parts of Phlomis younghusbandii has anti-inflammatory and anti-nociceptive effects, and that PF is found in the methanol extract. Inflammation is the key clinical manifestation of arthritis (42), thus, the anti-arthritic activity of PF in the AA model was investigated in the current study in order to determine whether PF is a major anti-arthritic constituent in Phlomis younghusbandii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that Phlomis Radix can be used to treat RA (26). For instance, Wang et al (27) demonstrated that the methanol extract from the aerial parts of Phlomis younghusbandii has anti-inflammatory and anti-nociceptive effects, and that PF is found in the methanol extract. Inflammation is the key clinical manifestation of arthritis (42), thus, the anti-arthritic activity of PF in the AA model was investigated in the current study in order to determine whether PF is a major anti-arthritic constituent in Phlomis younghusbandii.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the concentration at which PF induced acute toxicity to rats, they were treated with various concentrations of PF. Rats were randomly divided into 10 groups (n=10 per group), and were orally administered with 0, 20, 40, 60, 80, 100, 120, 140, 160 or 180 mg/kg PF, respectively (27). The acute toxicity test suggested that PF treatment up to the concentration of 180 mg/kg did not result in rat mortality within the observation period.…”
Section: Investigation Of the Effect Of Phlomisoside F On Complete Frmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, the spinal cord was quickly removed, an intact L4 ~ L6 dorsal root was cut and stored into -80 °C liquid nitrogen pending further experiments [19]. To evaluate the COX-2 expression in the dorsal horn of the spinal cord, total proteins of spinal cord tissue were extracted.…”
Section: Evaluation Of Effect Of Ta On Cox-2 In Formalin Induced Painmentioning
confidence: 99%
“…However, research and study on modern pharmacology of P. younghusbandii is not common. Over the years, several studies demonstrated that the root extracts of P. younghusbandii had anti-bacterial, analgesic and anti-inflammatory activities [7][8][9]. But whether the extracts or chemical components from Phlomis younghusbandii have anti-cancer activity has not been reported up to now.…”
Section: Introductionmentioning
confidence: 99%